Hubungan Efikasi Diri dan Stres Kerja Perawat Terhadap Pengetahuan Penatalaksanaan RJP Di IGD RSUD Brigjend H. Hasan Basry Kandangan - Fadli, M. Wahyuniar; Daud, Izma; Mira, Mira (LPPM Universitas Sari Mulia, 2023)
Background: American Heart Association has identified that 17.3 million deaths occur annually due to heart disease. Basic life support (BLS) is crucial in addressing sudden cardiac arrest, and healthcare professionals need to possess fundamental knowledge of BLS aspects and be proficient in cardiopulmonary resuscitation (CPR). The emergency environment induces stress, necessitating a high level of self-efficacy, particularly for nurses working in the Emergency Department (ED). While all healthcare professionals in hospitals are susceptible to stress, nurses experience higher stress levels. The research aims to explore the relationship between nurses' self-efficacy, job stress, and their knowledge of CPR management in the ED. Research Objective: To investigate the correlation between nurses' self-efficacy, job stress, and their knowledge of CPR management in the Emergency Department. Method: The research adopts a correlational approach with a cross-sectional design. The population includes all nurses working in the Emergency Department, with a total sample of 30 individuals selected through total sampling. The results of the study on nurses' self-efficacy related to CPR management knowledge, using the Spearman rho test, indicate a ρ value of 0.000 < α = 0.05, with an r value of 0.582, signifying a moderate level of relationship. The study also found a ρ value of 0.000 < α = 0.05 with an r value of 0.713, indicating a strong relationship between job stress and knowledge of CPR management. Conclusion: This research concludes that there is a relationship between nurses' self-efficacy, job stress, and their knowledge of CPR management in the Emergency Department of Brigjend H. Hasan Basry Kandangan Regional General Hospital.